CULTURAL DIVERSITY IN THREE MOTINGO BUSYE’S ROMANCE “POPULAR” NOVELS - -, Maizufri; Ratna, I Nyoman Kutha; Cika, I Wayan; Kusuma, I Nyoman Weda (e-Journal of Linguistics, 2014)
This study is entitled Cultural Diversity in Three Motingo Busye ’s Romance “Popular” Novels and explored three novels written by Motingo Busye (hereinafter abbreviated to MB), Fatimah Chen Chen, Hotel Halekulani , and Seribu Senja di Roma . It aimed at identifying the cultural styles used in the three novels using the theory of intertextuality proposed by Julia Kristeva. It investigated how the writer described the images of many cultures in the world narrated in the three novels using the sociological approach and psychological approach. It revealed the characterization of the main characters during their lives through the sequence of id, ego, and super ego. Apart from that, several cultural forms as to how the writer named the characters in the three novels were also investigated. The forms of cultural diversity found in the present study are as follows (1) out of 76 characters in the three novels coming from four countries, seven cities and regions, 38 forms of images coming Europe, America, and Asia (Taiwan and Indonesia) were found; (2) from the process of characterization of the main characters, as far as their images were concerned, it was found that the forms of cultural pluralism varied; they were samen leven (living together), polygamy, and the phenomenon of illegitimate children; (3) Apart from that, with regard to how the characters were named (the naming process), the three novels showed the nuance of cultural pluralism involving various cultures in the world. It turned out that how the so many characters were named needed high and wide awareness and knowledge of various cultures as the material of the essence of the images.
Keywords: cultural diversity, romance “popular” novels